2005
DOI: 10.1177/0885066604273497
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Use Precludes Prescription of Estimated Nitrogen Requirements

Abstract: The objective was to determine whether reducing enteral nutrition to accommodate 1% Propofol-derived energy results in suboptimal nitrogen prescription. This was a prospective observational study of 85 consecutive patients requiring mechanical ventilation and receiving 1% Propofol. Enteral nutrition prescription often failed to meet nitrogen requirements (<90%, in 50.6%; <80%, in 21.1%), whereas fat provided 51% of total energy input, exceeding 2 g fat/kg/d in 20%. However, gastroparesis was common, resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 53 publications
(63 reference statements)
2
32
3
1
Order By: Relevance
“…Previous studies in general medical and surgical critical care populations have also demonstrated a large contribution of delivered calories from propofol. 36 Enteral regimens are not routinely altered to account for lipid provisions or to prevent excessive lipid intake. Close supervision of propofol administration as an additional lipid source is clearly warranted in a critically ill population of SAH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in general medical and surgical critical care populations have also demonstrated a large contribution of delivered calories from propofol. 36 Enteral regimens are not routinely altered to account for lipid provisions or to prevent excessive lipid intake. Close supervision of propofol administration as an additional lipid source is clearly warranted in a critically ill population of SAH patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent reason for ICU admission was major trauma (n = 162, 43.8%). The median [IQR] APACHE II score was 19 [15][16][17][18][19][20][21][22][23][24], 80% required inotropes or vasopressors at some point during their ICU stay, and 65 (17.6%) did not survive to hospital discharge.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…15,16 In an attempt to compensate for energy provided by propofol, EN or PN volumes may be reduced. However this could result in inadequate delivery of protein, 17 particularly as underfeeding is already prevalent in this patient population; average energy delivery in ICUs internationally is reported to be 61%, 3,4 and average protein delivery is approximately 56% or 0.6 g/kg/d. 6 In our study, propofol did contribute a moderate proportion of energy in the first 48 hours, before reaching a stable level by day 3, an observation that is consistent with prior work.…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
“…A study by Taylor et al . () found that mechanically‐ventilated ICU patients who were administered propofol received an inadequate amount of protein to meet nitrogen needs at the same time as still maintaining energy balance. The Specialised Group received a statistically significant larger amount of modular protein (4.9 g); however, neither the protein from the modular component, nor the total protein intake had a direct impact on ICU days and the number of ventilator hours in the present study.…”
Section: Discussionmentioning
confidence: 99%